2009
DOI: 10.1097/ans.0b013e3181b0d6ef
|View full text |Cite
|
Sign up to set email alerts
|

Web-Based Weight Management Programs for Children and Adolescents

Abstract: More than 17% of children aged 6 to 19 years living in the United States are classified as overweight. Medical costs related to overweight and obesity were recently estimated to approximate $100 billion annually. The purpose of this systematic review was to provide the scientific evidence regarding Web-based weight management programs for overweight children and adolescents. Results suggest the potential for Web-based behavioral change programs for weight management in overweight children and adolescents. Futu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(41 citation statements)
references
References 39 publications
0
38
0
Order By: Relevance
“…This finding contradicts what others have found as family-based intervention have improved the success of traditional clinical interventions [22, 26]. However, these interventions focused on pre-adolescents or younger children, targeted the parents, and were delivered in person and in group-based settings and ensured that parents were actively engaged in the intervention [3]. One possible mechanisms through which parental participation could have influenced the outcomes of the current intervention is by changing the home environment to better support their adolescent’s health behaviors, [11] as the parent site provided them with advice on how to support the challenges and goals their adolescents were expected to achieve that week.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…This finding contradicts what others have found as family-based intervention have improved the success of traditional clinical interventions [22, 26]. However, these interventions focused on pre-adolescents or younger children, targeted the parents, and were delivered in person and in group-based settings and ensured that parents were actively engaged in the intervention [3]. One possible mechanisms through which parental participation could have influenced the outcomes of the current intervention is by changing the home environment to better support their adolescent’s health behaviors, [11] as the parent site provided them with advice on how to support the challenges and goals their adolescents were expected to achieve that week.…”
Section: Discussionmentioning
confidence: 72%
“…For example, a number of observational and longitudinal studies have shown that parents who use controlling practices such as pressuring the child to eat healthier food result in poor self-regulatory behaviours such as eating in the absence of hunger [8, 9]. Previous studies emphasize the importance of supporting change in children’s health behaviours at the household level; [3, 22] however, this study suggests the need in helping parents use more autonomy supportive parenting practices as it may explain why their engagement did not positively influence the outcome of the intervention. Future e-health interventions should better support parent/adolescent interactions, such as providing parents with the skills to use autonomy supportive approaches as a way to better support their adolescent and ultimately improve the efficacy of these interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Further we found no eHealth or mHealth (mobile device) interventions specifically intending to evoke the senses that guide food selection beyond the otherwise sight-sound realm of electronic media [39-43]. …”
Section: Discussionmentioning
confidence: 99%
“…In the context of group treatments, web- and mobile-technologies can serve to engage individuals in social networks remotely and can be used to encourage greater interaction among participants from in-person groups (61, 62) (63). Technology use has contributed to weight loss in adults (63) and increases peer-to-peer supportive interactions and perceptions of diet and exercise support and social interaction in adolescents (64).…”
Section: Future Directionsmentioning
confidence: 99%